Psycometric Characteristics of the Turkish Version of the Caregiver Vaccination Attitudes Scale - Sefa Sobcalı; Sevda Arslan (Galenos Publishing House, 2022)
Objective:This study aims to determine the psychometric properties of the Turkish version of the Caregiver Vaccination Attitudes Scale.Method:This methodologically designed study consists of parents (n = 220) of 12-35 months old children applying to the Department of Child Health and Diseases in one Research and Application Center for any reason between July 2020 and June 2021. The data were collected using the "Descriptive Information Form" and "Caregiver Vaccination Attitudes Scale" and the analysis was made by transferring them to IBM Statistical Package for the Social Sciences Statistics 23 and IBM Statistical Package for the Social Sciences AMOS 23 programs. Frequency distribution for categorical variables, descriptive statistics for numerical variables, exploratory and confirmatory factor analysis for scale validity, Cronbach's alpha value for reliability, and intraclass correlation coefficient analysis for test-retest reliability were used.Results:In the construct validity of the scale, the Kaiser-Meyer-Olkin value was found to be .951 and the Barlett's test showing its suitability for factor analysis was significant (p < .001). The scale consisted of 13 items and a single factor. The Cronbach's alpha coefficient was .941, and the total explained variance was 62.822%. The fit index values for the confirmatory factor analysis model of the scale were determined as χ2/df = 2.368, goodness of fit index = .908, normed fit index = .941, comparative fit index = .965, root mean square error of approximation = .079, and standardized root mean square residual = .035, and they were well-matched.Conclusion:The Caregiver Vaccination Attitudes Scale is a valid and reliable scale adapted to Turkish society, and it is sufficient and satisfactory in terms of distribution, measurement skill, internal consistency, and model fit.